The potential ability of Stethorus bifidus (Kapur) to regulate populations of Tetranychus lintearius (Dufour) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University - Peterson, Paul Gordon (Massey University, 1993)
Tetranychus lintearius Dufour (Acari; Tetranychidae) was released in New Zealand, in 1989, to assist in the regulation of gorse (Ulex europaeus). The present study was initiated to determine why colonies of GSM are consistently failing to establish above parallel 39°S and the possibility that Stethorus bifidus may be regulating populations of T.lintearius (GSM). Predation by S.bifidus was investigated by examining both numerical and functional responses to prey density. - Development of S.bifidus is described by a linear relationship with temperature between 8.5°C and 27.5°C (numerical response). Oviposition and temperature are linearly related and independent of GSM density. Measurements of temperature under GSM webbing showed an elevation of 1- 20 C above ambient. - The feeding rate of S.bifidus increased in a non-linear fashion between 6.5°C and 32.5°C (functional response). - Handling time decreased with increasing prey density demonstrating that S.bifidus is an effective predator at high mite densities. This investigation suggests that the role of S.bifidus in regulating GSM is more important in northern regions of New Zealand.
Keywords: Weeds; Gorse; Tetranychus lintearius; New Zealand; Biological control